PENGARUH PROGRAM KESEJAHTERAAN TERHADAP SEMANGAT KERJA KARYAWAN OUTSOURCING PADA PT ARINA MULTIKARYA - Sitio, Vera Sylvia Saragi (Feb Universitas Dirgantara Marsekal Suryadarma, 2020)
Nowadays, companies are required to understand what the employees needed.. Therefore,companies are faced with the challenge of how the human resources they have become potentials that cansupport and achieve company goals and have employee morale. Focus of this research on economic welfareprograms, namely incentives and health programs. The aims of this research is to analyze the effect of thewelfare program on employee morale at PT Arina Multikarya. The population is 251 people. The samplingtechnique is done by simple random sampling and using slovin formula, amounting to 154 respondents.Technique data analysis uses multiple linear regression analysis with using SPSS for MAC 24 software. Theresults of this research showed that incentives and health programs have a significant effect on thesignificant value 0,000 which is 30.8% of employee morale variables can be explained by incentives andwelfare programs while the remainder is explained by other variables not contained in the model.Keywords: Incentives, Health Programs, Employee Morale